Faktor-Faktor yang Mempengaruhi Agresivitas Remaja - Putri Rahmaning Sekar (Psyche 165 Journal, 2021)
Aggressiveness is the desire to hurt other individuals, by expressing negative feelings such as hostility to achieve the desired goal. The aggressiveness component consists of physical aggression, verbal aggression, anger, and hostility. The purpose of this study is to identify the factors that influence aggressiveness. Literature searches were carried out on the Researchgate, Scopus, Springer, and Google Schoolar electronic databases using the keywords "aggressive behavior and aggressiveness". The research strategy of this research is a kind of systematic literature review research using qualitative (meta-synthesis) methods. The approach used in this research is meta-ethnograph. Search results show that aggressiveness is influenced by internal and external factors. These internal factors include: frustration, thinking disorders and adolescent intelligence, as well as emotional / emotional disturbances in adolescents while external factors include family or peer factors, school factors and environmental factors.